Extraction of natural coagulant from peanut seeds for treatment of turbid water - Birima A.H.; Hammad H.A.; Desa M.N.M.; Muda Z.C. (Institute of Physics Publishing, 2023)
This study investigates the potential of peanut seeds as an environmental friendly and natural coagulant for the treatment of high turbid water. The peanut seeds have been used after oil extraction; and the active coagulation component was extracted by distilled water and salt solution of different salt concentrations. The salts used were NaCl, KNO3, KCl, NH4Cl and NaNO3. Synthetic water with 200 NTU turbidity was used. Peanut extracted with NaCl (PC-NaCl) could effectively remove 92% of the 200 NTU turbidity using only 20 mg/l, while peanut seeds extracted with distilled water (PC-DW) could remove only 31.5% of the same turbidity with the same dosage. The coagulant dosage did not affected by the concentration of the salt solution, however, residual turbidity decreased with increasing the concentration of the salt; and the relationship was found to be a second order polynomial curve with R2 of 0.9312. The other salts tested were also found to be good solvents to extract the active coagulation component with no much difference from NaCl solution in terms of efficiency. Published under licence by IOP Publishing Ltd.